Implementasi Aplikasi Keuangan Web Pt Zathco - Khairul Azis; Fauzi Kurniawan; Ikhsan Rifki (Lembaga Pengembangan Kinerja Dosen, 2024)
The system currently used is experiencing problems in handling using bookkeeping techniques which involve rewriting records into ledgers and then converting them to MS. Excel is to be produced as a financial report, so the report produced is late and inaccurate. problems in recording and reporting incoming and outgoing financial data, as well as in several months incoming and outgoing can reach targets. This often happens when recording financial data. This is caused by a helper or admin error. The administration department is recording data on money coming in and money going out. Additionally, accumulating a large number of filings can help record necessary financial data, and searching for filings can be time consuming as well as other tasks. The aim of this research is to develop an inventory management application that can manage money in or money out data, inventory data, and delivery data with agencies. This is a developer about a website that was created to simplify incoming money data and outgoing money data so that it can help business processes in the company. Web-based financial applications in companies have an important role in coordinating and accelerating company financial processes. With real-time access to financial data, this application allows management to track cash flow, combine transactions, and compile financial reports quickly and accurately. Budget management becomes more efficient, and the integration of online payment features makes the transaction process easier. In addition, the application supports audits and provides financial regulation, increasing the security of company data. In designing the interface and developing a web-based financial application system, namely identifying the company's business needs to ensure the application is in accordance with company policies and goals. Through user analysis and user experience (UX) design, intelligent and effective interfaces are developed. Wireframing and prototyping processes were used to design the application structure taking into account the specific needs of the research.